A heterogeinidade, as formações discursivas e os efeitos metafóricos no discurso religioso de membros da Assembléia de Deus - Silva, Dalexon Sérgio da (2012)
This study aims to examine the religious discourse of members of the Evangelical Church Assembly of God Field Abreu e Lima. This is the church that is pointed to by the Brazilian Institute of Geography and Statistics - IBGE, as it has the largest number of members among evangelical churches, both in Pernambuco and Brazil. Such interest in this paper arose from the observation that this research investigator in his positionsubject teacher of the public school system, realized in the speech of its students assembleianos the presence of many metaphorical effects, such as: - "He is a believer fire "or" - "I am a vessel in the hands of God", which sparked her interest in the research agenda. Thus, in light of the theoretical perspective and analytical procedures Discourse Analysis of French (AD), this paper aims to mobilize the concepts of heterogeneity discursive, discursive formations, discursive memory and the effects of metaphoric senses and analysis of a corpus by religious discourse assembleianos six subjects, four pastors and two believers. To this end, assumes the theoretical postulates defended by its main representatives, mainly by Pecheux, Europe and Orlandi, Indursky, Brandão and Mussalim in Brazil. This bias, the survey indicated the emergence of a new discursive formation, which resolved cognominar of "discursive formation of believer assembleiano interaction with the world," because unlike the discursive formation of precursor Christian Assembly of God, which denied any interactions with the world, this new FD that is present in the community assembleiana allows for some interaction with the "world", especially with regard to the uses and customs of the Christian Assembly of God.